Etiology of Acute Kidney Injury in Hospitalized Patients in a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Acute Kidney Injury (AKI) previously referred to as acute renal failure complicates acute care hospital admissions and intensive care unit patients. In AKI associated with sepsis and multiple organ failure, mortality is high and the outcome is usually determined bythe severity of the underlying disorder and other complications, rather than by kidney injury itself. Aim of our study was to evaluate the etiological profile of AKI in a tertiary care hospital like Chittagong Medical College Hospital (CMCH).  Materials and methods: This observational study was conducted among 100 hospitalized patients in different wards of CMCH from November 2018 to April 2019. Patients were selected based on the Kidney Disease Improving Global Outcomes (KDIGO) criteria of AKI. An increase in serum creatinine >0.3 mg/dl or >1.5 times the baseline and a fall of urine output